Observation of antiferromagnetic ordering from muon spin resonance study and the Kondo effect in a Dy-doped Bi2Se3topological insulator - Gangwar V.K.; Kumar S.; Singh M.; Singh P.; Ghosh L.; Pal D.; Shahi P.; Uwatoko Y.; Schwier E.F.; Shimada K.; Sharma D.K.; Kumar S.; Chatterjee S. (My University, 2025)
The transport and magnetic properties as well as the microscopic electronic properties of the Dy-doped topological insulator Bi2Se3 (Bi1.9Dy0.1Se3) are examined in detail. It is demonstrated that Dy doping induces antiferromagnetic (AFM) ordering in Bi2Se3. It is also observed that Dy doping opens a surface band gap of ∼52 meV at 6.5 K. The transition from AFM to ferromagnetic occurs at a lower temperature, ∼5 K in a magnetic field of ∼3 T. Furthermore, Dy doping in Bi2Se3 leads to the Kondo effect and weak localization to weak anti-localization crossover. Muon spin resonance measurements indicate that the signal measured with magnetization reflects the magnetic properties of 2% of the sample. The experimental findings are supported by theoretical calculations based on density functional theory. © 2021 IOP Publishing Ltd.